2006
DOI: 10.1002/hbm.20320
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of automatic beliefs about gender and race

Abstract: Functional MRI was used to identify the brain areas underlying automatic beliefs about gender and race, and suppression of those attitudes. Participants (n = 20; 7 females) were scanned at 3 tesla while performing the Implicit Association Test (IAT), an indirect measure of race and gender bias. We hypothesized that ventromedial prefrontal cortex areas (PFC) would mediate gender and racial stereotypic attitudes, and suppression of these beliefs would recruit dorsolateral prefrontal cortex (DLPFC) and the anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
147
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 106 publications
(113 reference statements)
16
147
0
1
Order By: Relevance
“…Beauregard and Paquette (2006) reported that mystical experience in nuns activated several brain areas throughout the brain including the ventral medial frontal cortex and subcortical structures (Figure 1). Shortly later, it was found that the anteromedial prefrontal cortex was activated when subjects made implicit associations involving consistent gender and racial stereotypes (Knutson et al , 2007 ). Han et al (2008) showed that personal trait judgments regarding the self or public persons showed signifi cantly greater activity of the mid-dorsal medial frontal cortex in Christian than in non-religious subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauregard and Paquette (2006) reported that mystical experience in nuns activated several brain areas throughout the brain including the ventral medial frontal cortex and subcortical structures (Figure 1). Shortly later, it was found that the anteromedial prefrontal cortex was activated when subjects made implicit associations involving consistent gender and racial stereotypes (Knutson et al , 2007 ). Han et al (2008) showed that personal trait judgments regarding the self or public persons showed signifi cantly greater activity of the mid-dorsal medial frontal cortex in Christian than in non-religious subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Schjoedt et al (2009) Personal prayer in religious subjects 8 20 50 Han et al (2008) Christian self-judgment 8 27 35 Sommer et al (2010) False belief attribution 4 34 40 Stern et al (2010) Greater uncertainty in sampling 6 33 30 Rothmayr et al (2011) Belief reasoning + inhibitory control 10 36 44 Beauregard and Paquette (2006) Mystical experience -11 52 13 Knutson et al (2007) Combined race and gender associations 20 51 9 Kapogiannis et al (2009) God ' s perceived involvement 9 66 6 Unauthenticated Download Date | 5/12/18 11:38 PM For the ' process of believing ' as it might appear in a religious or secular manner, we would like to coin the neologism ' credition ' . Credition is conceived as a psychological term in analogy to emotion and cognition that denotes the mental activity related to what we call ' he/she believes ' (Angel , 2006(Angel , , 2012.…”
Section: Theoretical Considerations Of Belief Processesmentioning
confidence: 99%
“…While both AI regions have been strongly implicated in self-processing, their role as a centre for interoceptive information processing means that they are also linked to the visceral representation of emotion and particularly negative affect (Nitschke, Sarinopoulos, MacKiewicz, Schaefer, & Davidson, 2006). Thus, it has been suggested that AI activation in prejudice studies represents the negative subjective feelings that participants experience when perceiving an out-group (Harris & Fiske, 2006;Knutson, Mah, Manly, & Grafman, 2007).…”
Section: Prejudice and The Conceptual Selfmentioning
confidence: 99%
“…In other words, automatic associations may not be expressed because of controlled processing. In order to address the problematic behavioral measurement of automatic aspects of attitudes, a small amount of neural research interested in the neural systems underlying prejudice has drawn on the Implicit Association Test (IAT: Greenwald et al, 1998) (Chee et al, 2000;Cunningham et al, 2004;Knutson et al, 2006;2007;Luo et al, 2006;Phelps et al, 2003;Phelps et al, 2000;Richeson et al, 2003). Although the IAT is one of the most popular behavioral measures of automatic (or implicit) attitudes, particularly for prejudice (Fazio and Olson, 2003), behavioral and modeling research suggests that IAT performance reflects both automatic and controlled processes (Conrey et al, 2005;Sherman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%